Chemotaxis of Pseudomonas syringae subsp. savastanoi Virulence Mutants - Soby, Scott (1991)
Several mutants of Pseudomonas syringae subsp. savastanoi were tested for their ability to sense and respond to a chemotactic gradient in low concentrations of yeast extract. The mutants were deficient in one or both of the genes coding for the synthesis of the plant hormones indole-3-acetic acid (IAA) and isopentenyl adenosine. Mutations which resulted in the loss of IAA production were due to the loss of the entire plasmid containing the iaa operon or to an 18-kb deletion of the iaa region. Additional mutants tested were deficient in their ability to produce isopentenyl adenosine as a result of the loss of the ptz-bearing plasmid. In all cases, strains which had lost the ability to produce IAA exhibited enhanced motility of up to 2.5 times that of the wild type (IAA(+)) in medium containing 0.01% yeast extract. No differences in motility were observed on medium containing lower concentrations of yeast extract. The presence or absence of the cytokinin plasmid and the presence or absence of inorganic nitrogen in the medium had no effect on the relative mobility of the strains.